Analysis of Posttranslational Activation of Alternative Oxidase Isoforms . Issue 4 (8th June 2017) - Selinski, Jennifer; Hartmann, Andreas; Kordes, Adrian; Deckers-Hebestreit, Gabriele; Whelan, James; Scheibe, Renate
Abstract : The multiple alternative oxidase isoforms from Arabidopsis are differentially activated by various metabolites, suggesting isoform-specific functions. Abstract: Mitochondrial alternative oxidase (AOX) in plants is a non-proton-motive ubiquinol oxidase that is activated by redox mechanisms and 2-oxo acids. A comparative analysis of the AOX isoenzymes AOX1A, AOX1C, and AOX1D from Arabidopsis ( Arabidopsis thaliana ) revealed that cysteine residues, CysI and CysII, are both involved in 2-oxo acid activation, with AOX1A activity being more increased by 2-oxo acids than that of AOX1C and AOX1D. Substitution of cysteine in AOX1A by glutamate mimicked its activation by pyruvate or glyoxylate, but not in AOX1C and AOX1D. CysIII, only present in AOX1A, is not involved in activation by reduction or metabolites, but substitutions at this position affected activity. AOX1A carrying a serine residue at position CysI was activated by succinate, while correspondingly substituted variants of AOX1C and AOX1D were insensitive. Activation by glutamate at CysI and CysII is consistent with the formation of the thiohemiacetal, while succinate activation after changing CysI to serine suggests hemiacetal formation. Surprisingly, in AOX1A, replacement of CysI by alanine, which cannot form a (thio)hemiacetal, led to even higher activities, pointing to an alternative mechanism of activation. Taken together, our results demonstrate that AOX isoforms are differentially activated and that activation at CysI and CysII is additive.